A study of device performance on the effects of integrating photodiode onto CMOS technology / Ziadora Ibrahim - Ibrahim, Ziadora (2008)
The execution of this project is to investigate the effects on device performances of integrating photodiode onto a 0.5um and 0.35um CMOS technology. The desired device performances that are desired to be observed are threshold voltage, saturation current and breakdown voltage. The methodology was carried out using a device modeling; SILVACO TCAD tools where the substrate layers and graphical results are observable. Factor that holds the reins of optimizing the threshold voltage is investigated. The device performances and electrical properties are observed and analyzed. As the investigation was undertaken, it can be bring to a close that the integration of photodiode onto a CMOS technology results in a decline manner for the threshold voltage and saturation current. Nevertheless, this negative effect may be resolved by optimizing the threshold voltage. On the contrary, the existence of photodiode results in a constructive manner for the breakdown voltage of NMOS technology.